PENENTUAN NILAI SPF EKSTRAK DAN LOSIO TABIR SURYA EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura L.) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Widyawati, Erni; Ayuningtyas, Nurista Dida; Pitarisa, Agustina Putri (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
Excessive and prolonged sun exposure can cause erythema and sunburn, premature aging and skin cancer. Kersen leaves contain total flavonoids and phenolics which can be used as active ingredients for making sunscreen lotion. This study was to determine the SPF value, the value of erythema transmission (% Te) and the value of pigmentation Transmission (% Tp) from extracts and lotions of kersen ethanol extract using the Uv-Vis spectrophotometric method. Absorbance increases at wavelengths of 290-400 nm at intervals of 5 nm. The results showed SPF extract values ​​with a composition of 500 ppm, 1000 ppm, and 2000 ppm combined - 12 were 12.15 (maximum ability); 17,29 (ultra protection); and 22.01 (ultra protection). % Te value 0.54; 0.16 and 0.05 all include the total block category,% value Tp 2.50; 1.30 and 0.49 (total blocks). Whereas for losio with a concentration of 0.5%, 1% and 2% respectively the SPF value produced is 3.61 (minimum protection); 8.18 (maximum protection) and 10.13 (maximum protection). % Te value 4.29 (extra protection); 1.58 (extra protection) and 0.99 (maximum protection). % value Tp 9.30; 4.22 and 2.80 are all included in the total block category. Keywords : kersen leaves, sunscreen lotion, SPF, erythema transmission, pigmentation transmission